Digitalisasi Pemberdayaan Melalui Dana Zakat Produktif Untuk Mengatasi Kemiskinan Di Kota Surabaya - Alfin Maulana; Erma Tri Wahyuningdyah (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
. This research aims to analyze the role of digitalization of productive zakat distribution by Baznas Surabaya to overcome poverty in the city of Surabaya. The aim of distributing zakat funds is not only consumption assistance, but also improving the productive economic conditions of zakat recipients. To achieve this goal, in facing current developments, it is necessary to digitalize the distribution of productive zakat funds appropriately. This type of research is qualitative research using a field approach (field research), with the hope of being able to photograph the effectiveness of digitizing the management of productive zakat funds. The results of this research show that digitizing the proper distribution of zakat funds can be carried out in a creative, productive way, namely distributing zakat that cannot be directly used or spent by mustahiq. So that its utilization makes it possible to have an economic impact on mustahiq by coaching and mentoring through digital technology